2022
DOI: 10.3389/fphys.2022.846003
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous Inflammatory Cytokines and Chemokines, Not Altered After Preoperative Adjunctive Conbercept Injection, but Associated With Early Postoperative Macular Edema in Patients With Proliferative Diabetic Retinopathy

Abstract: PurposeTo investigate the influence of preoperative adjunctive anti-VEGF drug (Conbercept) on vitreous inflammatory cytokines and chemokines profiles and whether those cytokines were associated with early macular edema (ME) after surgery for patients with proliferative diabetic retinopathy (PDR).MethodsIn this post hoc analysis of the CONCEPT clinical trial, subjects with PDR underwent vitrectomy were included and vitreous samples were collected at the start of vitrectomy. Levels of vitreous VEGF, 17 inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…A significant number of adherent leukocytes still seen in the EV - BZ group could be a possible reason for unaltered inflammation with this treatment. Also, the present study was not targeting hyperglycemia which could be contributing to inflammatory response as hyperglycemia is directly linked with increased levels of pro-inflammatory cytokines 58 Alternatively the dose of VEGF and duration of treatment also could be contributing to the effectiveness in suppressing the inflammation as both responsiveness and unresponsiveness were reported with anti - VEGF treatments 59 - 60 .…”
Section: Discussionmentioning
confidence: 99%
“…A significant number of adherent leukocytes still seen in the EV - BZ group could be a possible reason for unaltered inflammation with this treatment. Also, the present study was not targeting hyperglycemia which could be contributing to inflammatory response as hyperglycemia is directly linked with increased levels of pro-inflammatory cytokines 58 Alternatively the dose of VEGF and duration of treatment also could be contributing to the effectiveness in suppressing the inflammation as both responsiveness and unresponsiveness were reported with anti - VEGF treatments 59 - 60 .…”
Section: Discussionmentioning
confidence: 99%
“…[8] исходный уровень IL-7 у пациентов с ДМО значимо не отличался от контроля, а уровень IL-15 находился за пределами значений, подлежащих определению. В другой работе, где уровень ЦК измерялся у пациентов с пролиферативной диабетической ретинопатией с последующим развитием / без последующего развития макулярного отека после витрэктомии, содержание IL-7 и IL-15 в стекловидном теле не имело ни значимых различий исходно, ни влияло на риски развития ДМО [9]. При этом IL-7 описан как один из ЦК, уровень которых значимо снижается на фоне антиангиогенной терапии [10].…”
Section: Discussionunclassified
“…It has been reported that after preoperative intravitreal anti-VEGF injection, the VEGF level dramatically decreased, whereas the in uence on the vitreous in ammatory cytokines and chemokines in PDR was limited. 12 Moreover, the decreased halflives and increased clearance of anti-VEGF drugs in vitrectomized eyes probably also contribute. 27 Despite the preoperative intravitreal injection of anti-VEGF agent, a series of cytokines, including IL-1β, TNF-α, CXCL9, G-CSF, MCP-1, and RANTES, remained at a high level and may lead to PV-DME.…”
Section: Discussionmentioning
confidence: 99%
“…27 Despite the preoperative intravitreal injection of anti-VEGF agent, a series of cytokines, including IL-1β, TNF-α, CXCL9, G-CSF, MCP-1, and RANTES, remained at a high level and may lead to PV-DME. 12 Yoshida et al reported that elevated MCP-1 and IL-6 levels may indicate prolonged in ammation even after successful vitrectomy, which was signi cantly associated with PV-DME. 7 Rather than with an anti-VEGF agent, we found an intraoperative intravitreal TA injection effectively prevented PV-DME development in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation